A Critical Review of the Sexual Violence Crimes Law (UU TPKS) in Response to Child Sexual Violence Cases Based on 2024 Data - Muhammad Umar Kalibia; La Ilman Abu Naafi; Ide Raunas; Harmoko; Hardjito S.Darmojo (International Journal of Education, Vocational and Social Science, 2026)
This literature review aims to conduct a critical review of the effectiveness of the implementation of UU No 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) in responding to the high number of cases of sexual violence against children, as reflected in the 2024 data. Normatively, the UU TPKS is a progressive legal milestone that complements the UUPA, especially through expanding the definition of criminal acts such as Electronic-Based Sexual Violence (KSBE) and strengthening victims' rights to restitution and rehabilitation. However, the analysis results show significant implementation gaps. Data of 2024, which recorded more than 11,000 cases of child sexual violence and a sharp spike in KBGO cases (40.8%), proves that the UU TPKS has not had an optimal deterrent and preventive effect. This gap is triggered by three main obstacles: the absence of derivative regulations that hinder access to restitution, the cultural bias of law enforcement officers that leads to victim blaming, and operational challenges in proving KSBE cases. In conclusion, the effectiveness of the UU TPKS depends on addressing structural barriers and shifting cultural paradigms so that the principle of the best interests of the child can be fulfilled in a restorative manner.